(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Fungal strain Trichoderma spp. is a known bio control agent (BCA), which are difficult to obtain using more prevalent industrial-scale biofermentation methods such as submerged fermentation (SmF) However, difficult up-scalable solid-state fermentation (SSF) are appropriate for such BCA production. An automated semi-rotating drum bioreactor was developed and built to explore SSF scale-up using pea and wheat bran as substrates to valorise food-industry by-products into viable BCA ‘s. Estimation of biomass using CO2/O2 analysis in exhaust gasses revealed that mix of pea and wheat bran can produce a viable BCA ‘s using gentle mixing technique with possibilities of industrial scale-up